The simultaneous effect of moisture and pyrite on coal spontaneous combustion using CPT and R70 test methods (Rudarsko-geološko-naftni zbornik, 2019)
Among fossil fuels, coal is the most widely used all over the world for generating power and electricity and it is a stable source of energy. Despite all these benefits, coal mining has serious hazards, such as coal spontaneous combustion. There are many factors that influence the tendency for coal to spontaneously combust in coal mines. Pyrite can promote the risk of this phenomenon. This promotion is accelerated by the combination of pyrite and moisture content at the same time. This combination is very rarely discussed in literature. So, in this research, the accelerating effect of reactive pyrite and moisture content on coal spontaneous combustion was measured experimentally using crossing point temperature (CPT) and R70 test methods. For this purpose, a new experimental apparatus was assembled and made in Iran. Reaction rate data obtained from the experimental results showed that pyrite has a twofold action. It first catalyzes the oxidation reaction. Then, in a moist environment, pyrite is itself oxidized, which provides a secondary heat source, and so accelerates the process of coal spontaneous combustion. Since the pyrite oxidation reaction consumes moisture, there is a mutual effect of accelerated heating as less heat is used up in moisture evaporation. The results show that pyrite content can linearly accelerate the coal spontaneous combustion process, while moisture content under 20% increases it, and if the moisture exceeds 20%, the rate of this process is reduced. The results of this research are helpful in the assessment and management of coal spontaneous combustion issues in coal mines.